Solar uav: propulsion system - selection of motor and propeller for male uav - Ong, Chin Hwee (2014)
This report relooks at the propulsion system selection for the solar UAV and seeks to obtain a more accurate characterization of the motor-propeller combination in a bigger wind tunnel. In addition, the functionality of the motor over 24-hour operation at temperatures of -40°C is investigated in an environmental chamber.